TRANSPARENCY OF PROCUREMENT PROCESS AT THE MINISTRY OF FINANCE REPUBLIC OF INDONESIA - Ratnawati, Aryanti; Audita Setiawan; Ferry Ferdian Taufik; Louisiani Mansoni (Dinasti International Journal of Economics, Finance & Accounting, 2020)
Based on Theory of Planned Behavior, technology will facilitate the achievement of objectives. The process of procurement of goods and services at the Ministry of Finance Republic of Indonesia is carried out electronically, in the form of e-tendering and e-purchasing. Procurement with this technology makes the procurement process simpler, allowing the Ministry of Finance's Inspectorate General to carry out procurement with greater value and with shorter time. This study identifies and analyzes the e-tendering process and e-purchasing process towards the transparency of the procurement process of government goods and services . The conclusions is that e-tendering and e-purchasing contributed to transparency and showed that there was an influence between e-tendering and e-purchasing on the transparency of the process of procuring government goods and services at the Ministry of Finance of the Republic of Indonesia.